Extracellular vesicles of trypomastigotes of Trypanosoma cruzi induce changes in ubiquitin-related processes, cell-signaling pathways and apoptosis - Cornet Gomez, Alberto (2023)
Chagas disease is caused by the protozoan parasite Trypanosoma cruzi. The disease has an acute and a chronic phase in which approximately 30% of the chronic patients suffer from heart disease and/or gastrointestinal symptoms. The pathogenesis of the disease is multifactorial and involves the virulence of the strains, immunological factors and extracellular vesicles (EV) shed by the parasite which participate in cell–cell communication and evasion of the immune response. In this work, we present a transcriptomic analysis of cells stimulated with EV of the trypomastigote stage of T. cruzi. Results after EV-cell incubation revealed 322 differentially expressed genes (168 were upregulated and 154 were downregulated). In this regard, the overexpression of genes related to ubiquitin-related processes (Ube2C, SUMO1 and SUMO2) is highlighted. Moreover, the expression of Rho-GTPases (RhoA, Rac1 and Cdc42) after the interaction was analyzed, revealing a downregulation of the analyzed genes after 4 h of interaction. Finally, a protective role of EV over apoptosis is suggested, as relative values of cells in early and late apoptosis were significantly lower in EV-treated cells, which also showed increased CSNK1G1 expression. These results contribute to a better understanding of the EV-cell interaction and support the role of EV as virulence factors.